Facing Forward : Schooling for Learning in Africa - Bashir, Sajitha (Washington, DC: World Bank, 2018)
This book lays out a range of policy and implementation actions that are needed for countries in sub-Saharan Africa to meet the challenge of improving learning while expanding access and completion of basic education for all. It underscores the importance of aligning the education system to be relentlessly focused on learning outcomes and to ensuring that all children have access to good schools, good learning materials, and good teachers.